Dilemmas in recovery-oriented practice to support people with co-occurring mental health and substance use disorders: a qualitative study of staff experiences in Norway - Eva Brekke; Lars Lien; Kari Nysveen; Stian Biong (International Journal of Mental Health Systems, 2018)
Abstract Background Recovery-oriented practice is recommended in services for people with co-occurring mental health and substance use disorders. Understanding practitioners’ perceptions of recovery-oriented services may be a key component of implementing recovery principles in day-to-day practice. This study explores and describes staff experiences with dilemmas in recovery-oriented practice to support people with co-occurring disorders. Methods Three focus group interviews were carried out over the course of 2 years with practitioners in a Norwegian community mental health and addictions team that was committed to developing recovery-oriented services. Thematic analysis was applied to yield descriptions of staff experiences with dilemmas in recovery-oriented practice. Results Three dilemmas were described: (1) balancing mastery and helplessness, (2) balancing directiveness and a non-judgmental attitude, and (3) balancing total abstinence and the acceptance of substance use. Conclusions Innovative approaches to practice development that address the inherent dilemmas in recovery-oriented practice to support people with co-occurring disorders are called for.